Theoretical and experimental investigation of the dynamic behaviour of a standing-wave thermoacoustic engine with various boundary conditions. (August 2018) - Chen, Geng; Tang, Lihua; Mace, Brian R.
Highlights: Theoretical models to predict the onset temperature and frequency were developed. Viscous and thermal losses in the fluid and energy dissipation at the boundaries were considered. Effects of acoustic radiation and deformable endplate on the onset characteristics were studied. Distributions of acoustic field at onset condition were predicted. Experimental prototype was built to validate the theoretical predictions. Abstract: This paper investigates the dynamic behaviour of a one-dimensional, standing-wave thermoacoustic engine with various boundary conditions. The thermoacoustic engine is composed of an acoustic tube and a ceramic stack with two heat exchangers. The tube has one end open and the other end closed with a deformable plate whose boundaries are constrained. Theoretical models are developed based on the acoustic wave equations and the linear theory of thermoacoutics and validated by experiment. With the validated theoretical models, a parametric study is performed to investigate the influence of the boundary conditions at both ends of the tube. It is found that acoustic radiation at the open end and the presence of the deformable structure at the closed end not only influence the onset temperature and frequency of the system, but also affect the acoustic field along the tube. The developed theoretical models and experimental method in this study provide useful guidelines for the design of thermoacoustic engines for potential energy harvesting systems.